Ensino/aprendizagem da língua inglesa: um estudo comparativo nas Escolas Públicas X Particulares de ensino médio na cidade de Macapá - NUNES, Benedito da Costa (UNIFAP – Universidade Federal do Amapá, 2022)
This work has like one objective to contribute for one reflection about that teaching/learning‟s proceduring of the English in the Macapá City, checking how happens this process in traditional schools, that to long of that school‟s life serve to example to others schools. Emphasizing the role of the teacher of English like one of principals‟ examples in formation of the students creating the mechanisms having in view one profound transformation be it of a social nature, cultural, professional. This way, the research had certified that the teaching establishments public system observed, they did show one absence absurd to responsibilities to offer the conditions favorable in respect saying to languages learning, like fulfillment of the times, supports like material educational, lack of infrastructure and etc. To other side, the private schools did show been so prepared to develop teaching of English that are situated in the bulge of the PCN-Teaching English. One did see too one oscillation in respect to say to formation of the teachers observed, so nor at all could possess a grading to teach the English, but they had taught to have a free-course of language it has in view superficial communication of the teaching English. Before that view has been saw that teachers of the public schools had used the method traditional, which it gives a direction to teaching English to use of the grammar prescriptive English, across the translation and memorization of words. But now the teachers of the private system had used material educational to give class in Language English, giving some freedom to students to participate in class using the language English, what demonstrates in these schools is used the Method Communicative Actionable, because the students are free to create and act in classroom where the teacher is just a collaborator. However, in spite of differences extant in formation of the teachers, all them had fetched to carry out their class of best way possible, putting to proof too that school is responsible in to raise somebody‟s awareness of the responsibility of your role in the proceduring student‟s formation is related as in the formation teacher‟s continuity, modernization of the class using video class, laboratory of computers, books up-to-date and etc.